HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU MEROKOK PADA REMAJA LAKI-LAKI DI RW 016 KELURAHAN PAMULANG TIMUR - Sondang Deri Maulina Pasaribu; Widya Gita Oktaviana (STIKes IMC Bintaro, 2021)
Smoking behavior is a serious problem for Indonesia at this time, especially for adolescents, because some teenagers in Indonesia have considered that smoking is a necessity that cannot be avoided such as the need for